Seeds for needs: perceptions on climate change - Gevel, Jeske M.J, van de; Gellaw, A; Fadda, Carlo (2013)
Ethiopia is known for having a high diversity of durum wheat landraces. Most farmers in East Shewa’a have been replacing their landraces with modern varieties. These uniformly performing varieties require significant amount of external inputs and have less genetic variability and adaptive capacity to grow under more extreme climatic conditions. With changing climatic conditions there is a need for crops and varieties that can be grown in harsher environments. This project focuses on durum wheat and barley which are important cereals in the smallholders’ production systems.